Effects of oral passive immunization against somatostatin‐14 on growth performance, body composition and IgY delivery in rainbow trout (Oncorhynchus mykiss) and common carp (Cyprinus carpio). (27th January 2016) - Winkelbach, A.; Wuertz, S.; Schade, R.; Witkowski, P.T.; Steibli, A.; Meyer, S.; Schaefer, F.; Schulz, C.
Abstract: Egg‐yolk antibodies (IgY) against somatostatin‐14 (anti‐SST‐14) were evaluated as orally administered, growth promotants in gastric rainbow trout ( Oncorhynchus mykiss ) and agastric common carp ( Cyprinus carpio ) in an 8‐week feeding trial. Feeding groups were compared with fish which did not receive anti‐SST‐14 IgY. Growth responses and IgY plasma contents of the blood were assessed. In contrast to rainbow trout, oral anti‐SST‐14 addition to carp significantly improved protein efficiency ratio (PER, 1.02 ± 0.04) and protein productive value (PPV, 26.7 ± 0.91) after 56 days ( P  < 0.05) compared to the negative control (PER = 0.91 ± 0.02; PPV = 22.9 ± 0.66). IgY was undetectable in plasma of rainbow trout after oral administration, indicating that gastric degradation of the fed IgY makes this application route for growth promotion in gastric trout challenging.